Geophysical Exploration And Resource Assessment Of Deepwater Polymetallic Sulfide Deposits, Papua New Guinea - M. E. Williamson (International Marine Minerals Society, 2005)
From December 2004 through March of 2005 an extensive geophysical program was conducted to delineate polymetallic sulfide deposits in the Bismark Sea for a major mining concern. Deeply towed sidescan sonar, interferometric swath bathymetry, subbottom profiling, magnetic gradiometry, electrical resistivity, induced polarization. self-potential, gravimetry, water temperature/conductivity and towed video were among the methodologies tested against known occurrences of polymetallic sulfides in 1500 m -- 2200 m water depths. Known active and currently inactive sulfide areas were characterized using the various remote sensing techniques followed by survey with these same tools in other areas where they successfully discovered new prospects. Dredge sampling was used to ground truth both previously known sulfide areas and newly found deposits.